Light-emitting conjugated polymer capable of being photoetched, preparation method and application
By introducing azide groups on the side chains of fluorene structural units, the photolithographic luminescent polymer is developed, which solves the complexity of patterning processing of luminescent polymer films and realizes patterning of high-precision, micron-scale pixel arrays and simplified preparation of organic optoelectronic devices.
Patent Information
- Application Number
- CN202411596263.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The prior art is difficult to achieve high-precision, micron-scale pixel array patterning processing of luminescent polymer films, and the traditional lithography process is complex and is not suitable for multi-layer structure construction of organic optoelectronic devices.
By introducing azide groups on the side chains of the fluorene structural unit, a photolithographic luminescent polymer with azide groups is developed, and the patterning processing of organic semiconductor films is achieved using a direct photolithography process.
Direct photolithography patterning of luminescent polymer films is realized, the preparation steps of organic integrated optoelectronic devices are simplified, and the excellent solution processing characteristics and high luminous efficiency are achieved.
Smart Images

Figure CN119431747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer semiconductor materials, and in particular relates to a photolithographic luminescent conjugated polymer containing an azide group on the side chain, and a preparation method and application thereof. Background Art
[0002] Printing display technology has become a hot topic in the field of organic electroluminescence (OLED) in recent years due to its advantages in the manufacturing and cost of medium and large-sized panels. Among them, light-emitting conjugated polymers have great application potential in the field of flexible and printed displays due to their excellent optoelectronic properties and solution film-forming properties, as well as the unique mechanical properties of polymers. However, how to process light-emitting polymer films into high-precision, micron-level pixel arrays is the key to realizing the application of light-emitting polymers in the printing display industry. Photolithography is a core link in the field of integrated circuit and semiconductor manufacturing, but traditional photolithography processes require the use of photoresists, and at least six steps such as exposure, development, etching, and cleaning can be used to prepare a layer of pattern. The process is complicated and is not suitable for the construction of multi-layer organic structures of organic optoelectronic devices. Therefore, the development of light-emitting polymer materials that can be directly and efficiently patterned by photolithography is an important way to prepare high-resolution pixel-level display arrays by solution printing. Summary of the invention
[0003] The purpose of the present invention is to provide a photolithographic luminescent polymer containing an azide group on the side chain and a preparation method and application thereof, and to achieve direct photolithographic patterning of luminescent polymer films by introducing an azide group on the side chain of a fluorene structural unit.
[0004] To achieve the above object, the present invention adopts the following technical solution:
[0005] In a first aspect, the present invention provides a polymer, the structural formula of which is shown in the following formula I:
[0006]
[0007] In formula I, R1 is selected from one of the alkyl chains containing methylene in C1-C50;
[0008] The number average molecular weight of the polymer represented by Formula I is 10,000-100,000, specifically 15 kDa;
[0009] In Formula I, Ar is selected from an aromatic ring, a heteroaromatic ring, an aromatic ring or a heteroaromatic ring containing a long alkyl chain substituent; preferably, Ar is selected from any one of the following structural formulas:
[0010]
[0011] In the formula, R is selected from any one of the alkyl chains containing methylene in C1-C50;
[0012] represents the bonding position in structural formula I.
[0013] In a second aspect, the present invention provides a method for preparing the polymer of formula I, comprising: subjecting a compound of formula II and a compound of formula III to a carbon-carbon coupling reaction in an organic solvent in the presence of an inert atmosphere and a catalyst to obtain a polymer of formula I:
[0014]
[0015] In formula II-III, R1 and Ar are defined the same as in formula I.
[0016] In the above preparation method, the gas of the inert atmosphere is nitrogen or argon.
[0017] In the above preparation method, the catalyst is methanesulfonic acid (tri-tert-butylphosphino)(2'-methylamino-1,1'-biphenyl-2-yl) palladium (II) (abbreviated as Pd-P(t-Bu)3-G4), and trimethylsilanol potassium (abbreviated as TMSOK) is used as the alkaline substance.
[0018] In the above preparation method, the molar ratio of the compound represented by formula II, the compound represented by formula III, the catalyst and the alkaline substance is 1:1:0.05:2.2.
[0019] The temperature of the carbon-carbon coupling reaction is 35° C. and the reaction time is 72 hours.
[0020] The organic solvent for the carbon-carbon coupling reaction is anhydrous toluene.
[0021] Furthermore, the preparation steps of the compound represented by formula II include:
[0022] Under an inert atmosphere, the compound represented by Formula IV and diphenylphosphoryl azide (DPPA for short) are subjected to a nucleophilic aromatic substitution reaction under the action of 1,8-diazobispiro[5.4.0]undec-7-ene (DBU for short) to convert the hydroxyl group on the benzyl alcohol into an azide group to obtain a compound represented by Formula II:
[0023]
[0024] In the method for preparing the compound of formula II, the molar ratio of the compound represented by formula IV to the N3 group in diphenylphosphoryl azide is 1:2 to 10;
[0025] The reaction temperature is 45°C and the reaction time is 24 to 36 hours;
[0026] The reaction solvent is tetrahydrofuran;
[0027] The gas of the inert atmosphere is nitrogen or argon.
[0028] In a third aspect, the present invention provides the use of the polymer represented by formula I in at least one of the following (1) to (4): (1) dissolved in an organic solvent and processed into a uniform light-emitting film through a solution; (2) used as a polymer semiconductor photoresist by itself and patterned by a direct photolithography process; (3) used as a universal cross-linking agent in the photolithography patterning of organic semiconductors; (4) used in the preparation of organic optoelectronic devices.
[0029] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0030] 1. The raw materials used in the synthesis of the present invention are convenient and easy to obtain. Compared with the method of synthesizing the azide group using sodium azide, the synthesis process is safer and easy to industrialize and mass produce;
[0031] 2. The polymer of the present invention has excellent solution processing characteristics, good film-forming properties and high luminous efficiency;
[0032] 3. The polymer of the present invention can realize patterning of organic semiconductor thin films through direct photolithography, which is simple and convenient, and greatly simplifies the preparation steps of organic integrated optoelectronic devices;
[0033] 4. The polymer of the present invention can undergo cross-linking reaction with other polymers containing long alkyl chains, and can be used as a cross-linking agent in the cross-linking and curing of polymer films. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is the compound IV in Example 1 of the present invention 1 H-NMR spectrum;
[0035] Figure 2 is the compound IV in Example 1 of the present invention 13 C-NMR spectrum;
[0036] Figure 3 is the compound II in Example 1 of the present invention 1 H-NMR spectrum;
[0037] Figure 4 is the compound II in Example 1 of the present invention 13 C-NMR spectrum;
[0038] Figure 5 is the polymer of formula I in Example 2 of the present invention 1 H-NMR spectrum;
[0039] Figure 6is the polymer of formula I in Example 3 of the present invention 1 H-NMR spectrum;
[0040] Figure 7 This is a direct photolithography patterning diagram of the polymer PFO-alt-AzDPF film in Example 4 of the present invention;
[0041] Figure 8 Spectral properties of toluene solution and film of polymer PFO-alt-AzDPF in Example 4 of the present invention;
[0042] Fig. 9 Spectral properties of toluene solution and film of polymer FAzBT in Example 5 of the present invention;
[0043] Fig.10 This is a schematic diagram of the structure of a polymer electroluminescent device in Embodiment 6 of the present invention;
[0044] Fig.11 This is a performance curve diagram of the polymer electroluminescent device in Example 6 of the present invention. DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.
[0046] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should be the common meanings understood by those skilled in the art to which the present invention belongs. The raw materials, reagents, etc., unless otherwise specified, can all be obtained from public commercial channels.
[0047] Example 1
[0048] Synthesis of compound of formula II (wherein R1 is hexyl):
[0049]
[0050] 1. Synthesis of the compound of formula IV (in formula IV, R1 is hexyl), the specific synthesis route is as follows:
[0051]
[0052] The specific reaction step conditions are as follows:
[0053] (1) Synthesis of product Br-PhMeOH: Compounds p-hydroxybenzyl alcohol (8.10 mmol) and 1,6-dibromohexane (12.15 mmol) were dissolved in 10 mL of acetone, and potassium carbonate (16.64 mmol) was added to react at room temperature for 48 h. After the reaction was completed, dichloromethane and water were used for multiple liquid extractions. After that, the organic phase was subjected to reduced pressure distillation, silica gel column chromatography, drying and other steps to obtain the product Br-PhMeOH.
[0054] (2) Synthesis of DBFOH: Compound 2,7-dibromo-9-fluorenone (17.75 mmol) and phenol (30.70 mmol) were dissolved in 45 mL of methanesulfonic acid (MeSO3) and reacted at 50°C for 12 h. After the reaction, the reaction was quenched with 10 mL of saturated sodium chloride aqueous solution, and then separated and extracted with dichloromethane. After that, the organic phase was subjected to reduced pressure distillation, silica gel column chromatography, and drying to obtain the product DBFOH (15.74 mmol, yield 88.7%).
[0055] (3) Compounds Br-PhMeOH (1.97 mmol) and DBFOH (9.85 mmol) were dissolved in 10 mL of acetone, and potassium carbonate (7.23 mmol) was added, and the mixture was reacted at 90°C for 48 h. After the reaction was complete, 10 mL of water was added to quench the reaction, and then dichloromethane was used for separation and extraction. After that, the organic phase was subjected to reduced pressure distillation, silica gel column chromatography, and drying to obtain compound IV (1.09 mmol, yield 55.3%). The structural confirmation data are shown in FIG. Figure 1 and Figure 2 As shown: 1 H-NMR(400MHz, CDCl3)δ7.56(d,2H),7.45(dd,4H),7.27(s,2H),7.26(d,2H),7.03(d ,4H),6.86(d,4H),6.75(d,4H),4.60(s,4H),3.93(dt,8H),1.78(d,8H),1.50(d,8H); 13 C-NMR(101MHz)δ158.81,158.24,153.79,137.94,136.42,133.02,130.84,129.34,129. 10,128.75,121.88,121.65,114.63,114.42,67.89,65.20,64.42,63.00,29.27,25.97.
[0056] 2. Synthesis of the compound of formula II, the specific synthetic route is as follows:
[0057]
[0058] The specific reaction step conditions are as follows:
[0059] Compound IV (1.09 mmol) was dissolved in 10 mL of tetrahydrofuran, and then compound DBU (5.26 mmol) was added, followed by slow addition of DPPA (4.90 mmol), and the mixture was reacted at 45 °C in a nitrogen atmosphere in the dark for 36 hours. After the reaction was completed, 1 mL of saturated sodium bicarbonate solution was added to quench the reaction, and then water and dichloromethane were used for multiple extractions. Afterwards, the organic phase was subjected to reduced pressure distillation, silica gel column chromatography, and drying to obtain compound II (0.88 mmol, yield: 80.3%). The structural confirmation data are as follows: Figure 3 and Figure 4 As shown: 1 H-NMR(400MHz, CDCl3)δ7.57(d,2H),7.46(s,4H),7.35(s,2H),7.22(d,6H),7.04(d ,4H),6.89(d,4H),6.76(d,4H),4.25(s,4H),3.94(d,8H),1.81(s,8H),1.52(s,8H); 13 C-NMR(101MHz)δ159.23,158.25,153.80,137.95,136.43,129.91,129.35,129.11,127. 27,125.72,121.89,121.66,120.23,114.82,114.43,67.89,64.45,54.51,29.26,25.94.
[0060] Example 2
[0061] Synthesis of a polymer of formula I (in formula I, R1 is hexyl and Ar is 9,9-dioctylfluorene), the polymer is named PFO-alt-AzDPF:
[0062]
[0063] The synthetic route is as follows:
[0064]
[0065] Compound II (0.20 mmol) and 9,9-dioctylfluorene-2,7-diboronic acid dipinacol ester (0.20 mmol) were added to a 10 mL Shrek tube, and then the catalysts methanesulfonic acid (tri-tert-butylphosphino) (2'-methylamino-1,1'-biphenyl-2-yl) palladium (II) (Pd-P(t-Bu)3-G4, 0.01 mmol) and trimethylsilanol potassium (TMSOK, 0.44 mmol) were added, and after nitrogen was pumped three times, 2 mL of anhydrous toluene was added, and the reaction was allowed to react at a temperature of 35 ° C and a nitrogen atmosphere for 72 hours. After that, 0.5 mL of bromobenzene and 0.5 mL of phenyl borate were added to the reaction solution for end-capping, and the reaction was carried out for 6 hours respectively. After the reaction was completed, the reaction solution was dripped into 100 mL of methanol for precipitation, and a solid product was obtained by suction filtration. The obtained solid was extracted by Soxhlet extraction with acetone and n-hexane to remove unreacted raw materials and oligomers, and finally the target product was extracted with chloroform. Finally, the chloroform solution containing the target product was concentrated by vacuum distillation, and then precipitated with methanol again. The final target polymer PFO-alt-AzDPF was obtained by suction filtration and drying. The relative molecular weight (M) of the polymer was obtained by GPC test. n ) is 1.5 kDa. The structural confirmation data are as follows Figure 5 As shown: 1 H-NMR (400MHz, CDCl3) δ7.88(d,2H),7.77-7.71(m,2H),7.70(s,4H),7.54(s,4H),7.29(d,4H),7.21(d,4H),6.88(d,4H) ,6.82(d,4H),4.24(s,4H),3.95(t,8H),1.80(s,8H),1.52(s,8H),1.40(s,2H),1.26(s,2H),1.13(d,24H),0.78(d,8H).
[0066] Embodiment 3:
[0067] Synthesis of a polymer of formula I (wherein R1 is hexyl and Ar is 2,1,3-benzothiadiazole), the polymer is named FAzBT:
[0068]
[0069] The synthetic route is as follows:
[0070]
[0071] Compound II (0.4mmol) and 4,7-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-2,1,3-benzothiadiazole (0.4mmol) were added to a 10mL Shrek tube. Then, the catalysts methanesulfonic acid (tri-tert-butylphosphino) (2'-methylamino-1,1'-biphenyl-2-yl) palladium (II) (0.02mmol) and trimethylsilanol potassium (0.88mmol) were added respectively, and after nitrogen was pumped 3 times, 2mL of anhydrous toluene was added, and the reaction was allowed to react at a temperature of 35°C and a nitrogen atmosphere for 72 hours. 0.5mL of bromobenzene and 0.5mL of phenylboronic acid ester were added to the reaction solution for end-capping, and the reaction was carried out for 6 hours respectively. After the reaction was completed, the reaction solution was dripped into 100mL of methanol for precipitation, and a solid product was obtained by suction filtration. The solid product was dissolved in dichloromethane, poured into a neutral alumina column for chromatography, and then distilled under reduced pressure, concentrated and dried to obtain a polymer. Finally, the product FAZBT was extracted by Soxhlet extraction with acetone to remove unreacted raw materials and oligomers, and the target product FAZBT was extracted. The polymer NMR was as follows: Figure 6 As shown: 1 H-NMR(400MHz, CDCl3)δ8.08(d,2H),7.99(s,4H),7.72(s,2H),7.30(d,4H),7.18(d,4H), 6.85(d,4H),6.78(d,4H),4.21(s,4H),3.92(t,8H),1.75-1.77(m,8H),1.51-1.45(m,8H).
[0072] Example 4
[0073] A photolithographic patterned light-emitting film is prepared based on the polymer represented by formula I of the present invention:
[0074] The polymer PFO-alt-AzDPF prepared in Example 2 of the present invention was dissolved in a toluene solution at a concentration of 8 to 10 mg / mL. Then, the solution was evenly spin-coated on a pre-cleaned glass sheet using a spin coater at a speed of 1500 rpm to obtain a uniform film with a thickness of about 35 to 40 nm. After that, a mask with a hollow pattern was covered on the film and irradiated with a 365 nm ultraviolet LED lamp for 2 to 10 seconds with a light power of about 20 mW / cm 2 At this time, the exposed part of the film will be cross-linked. Finally, the exposed film is soaked in chlorobenzene for 5 seconds, fully developed, taken out, rinsed with deionized water and blown dry with nitrogen, and the patterned preparation of a square dot matrix of 40×40μm can be achieved. The specific patterning example is Figure 7 As shown. Combined Figure 8 From the spectra shown, it can be found that the absorption and emission peak positions of the polymer film remain almost unchanged before and after photolithography.
[0075] Example 5
[0076] A photolithographic patterned light-emitting film is prepared based on the polymer represented by formula I of the present invention:
[0077] The polymer FAzBT prepared in Example 3 of the present invention was dissolved in a toluene solution at a concentration of 8 to 10 mg / mL. Then, the solution was evenly spin-coated on a pre-cleaned glass sheet using a spin coater at a speed of 1500 rpm to obtain a uniform film with a thickness of about 35 to 40 nm. After that, a mask with a hollow pattern was covered on the film and irradiated with a 365 nm ultraviolet LED lamp for 2 to 10 seconds with a light power of about 20 mW / cm 2 At this time, the exposed part of the film will be cross-linked. Finally, the exposed film is soaked in chlorobenzene for 5 seconds, fully developed, taken out, rinsed with deionized water and blown dry with nitrogen, and the patterned preparation of a square dot matrix of 40×40μm can be achieved. Fig. 9 From the spectra shown, it can be found that the absorption and emission peak positions of the polymer film remain almost unchanged before and after photolithography.
[0078] Embodiment 6:
[0079] Application of the polymer PFO-alt-AzDPF according to Example 2 of the present invention as a crosslinking agent in a polymer light-emitting diode:
[0080] On a cleaned indium tin oxide (ITO) glass substrate, a layer of poly (3,4-ethylenedioxythiophene) - poly (styrene sulfonic acid) (PEDOT: PSS) was first spin-coated as a hole injection layer with a thickness of about 40nm, and annealed in air at 120°C for 20min. Then, the polymer PFO-alt-AzDPF prepared in Example 2 of the present invention was used as a cross-linking agent, and the blue light polymer poly [4-octyloxy-(9,9-diphenylfluorene)] (PODPF) was prepared into a toluene solution at a mass ratio of 1:9, with a concentration of 10mg / mL, and was evenly spin-coated on the PEDOT: PSS layer as a light-emitting layer with a thickness of about 40-50nm, and then transferred to a glove box for annealing (120°C, 15min). After that, the processed wafer was transferred to a vacuum deposition chamber, where 20 nm of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) and 0.8 nm of lithium fluoride (LiF) were deposited as electron transport and injection layers, respectively. Finally, 100 nm of aluminum (Al) was deposited as the cathode. The resulting device structure is shown below. Fig.10 The device performance curve is shown in Fig.11 As shown, the device has a start voltage of 4.6V and a maximum luminous brightness of 670cdm -2The maximum external quantum efficiency (EQE) is 0.65%, and the emission peak of the electroluminescence spectrum is 480nm, which proves the potential application value of the polymer as a cross-linking agent in the field of polymer electroluminescence.
[0081] The present invention has been disclosed above with preferred embodiments, but they are not intended to limit the present invention. Any technical solutions obtained by adopting equivalent replacement or equivalent transformation solutions fall within the protection scope of the present invention.
Claims
1. A polymer, characterized in that Its structural formula is shown in the following formula I: In the formula, Ar is selected from an aromatic ring, a heteroaromatic ring, an aromatic ring or a heteroaromatic ring containing a long alkyl chain substituent; R1 is selected from one of the alkyl chains containing methylene in C1-C50; The number average molecular weight of the polymer represented by formula I is 10,000-100,000.
2. The polymer according to claim 1, characterized in that Ar is selected from any one of the following structural formulas: In the formula, R is selected from any one of the alkyl chains containing methylene in C1-C50; represents the bonding position in structural formula I.
3. The method for preparing a polymer according to claim 1, characterized in that: include: In the presence of an inert atmosphere and a catalyst, the compound represented by Formula II and the compound represented by Formula III are subjected to a carbon-carbon coupling reaction in an organic solvent to obtain a polymer represented by Formula I: In formulae II to III, R1 and Ar are defined the same as in formula I.
4. The method for preparing a polymer according to claim 3, characterized in that: The catalyst is (tri-tert-butylphosphino) (2'-methylamino-1,1'-biphenyl-2-yl) palladium (II) methanesulfonate, and potassium trimethylsilanol is used as the alkaline substance.
5. The method for preparing a polymer according to claim 4, characterized in that: The molar ratio of the compound represented by formula II, the compound represented by formula III, the catalyst and the alkaline substance is 1:1:0.05:2.
2.
6. The method for preparing a polymer according to claim 3, characterized in that: The temperature of the carbon-carbon coupling reaction was 35° C. and the reaction time was 72 hours.
7. The method for preparing a polymer according to claim 3, characterized in that: The organic solvent for the carbon-carbon coupling reaction is anhydrous toluene.
8. The method for preparing a polymer according to claim 3, characterized in that: The preparation steps of the compound shown in formula II include: Under an inert atmosphere, the compound represented by formula IV and diphenylphosphoryl azide are subjected to a nucleophilic aromatic substitution reaction under the action of 1,8-diazobispiro[5.4.0]undec-7-ene to convert the hydroxyl group on the benzyl alcohol into an azide group to obtain a compound represented by formula II:
9. The method for preparing a polymer according to claim 8, characterized in that: In the preparation steps of the compound represented by formula II, one or more of the following conditions are met: The molar ratio of the compound represented by formula IV to the N3 group in diphenylphosphoryl azide is 1:2 to 10; The reaction temperature is 45°C and the reaction time is 24 to 36 hours; The reaction solvent is tetrahydrofuran.
10. Use of the polymer according to claim 1 in at least one of the following (1) to (4): (1) use in the preparation of light-emitting thin films; (2) use itself as a polymer semiconductor type photoresist and patterning through a direct photolithography process; (3) use as a universal cross-linking agent in the photolithography patterning of organic semiconductors; (4) use in the preparation of organic optoelectronic devices.
Citation Information
Patent Citations
Positive photosensitive polyimide resin composition with ester bond connected fluorene unit and siloxane
CN105301902A
Organic light emission diode device and application thereof
CN107068887A
Polymer semi-conductive photoresist with side chain containing azide group as well as preparation method and application of polymer semi-conductive photoresist
CN114479020A
Photosentitive resin composition having good low-temperature curing properties
KR100649651B1
Wafer-level package and method for production thereof
US20050173809A1